Pemberdayaan Aparatur Pemerintah Terhadap Prestasi Kerja Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Bombana - Fauzan, Roman Fikri; Alam, Syamsul; Basri, Muhammad (Universitas Halu Oleo, 2020)
The purpose of this research is to determine the empowerment of government officials on work performance in the personnel agency and human resource development in Bombana district. The research methodology used in this study is a descriptive method that seeks to describe the intended phenomenon. The data obtained from the results of interviews with informants, namely 4 people who are directly involved in the process of empowering the apparatus on employee performance achievements. Then the data obtained is then analyzed and interpreted and a conclusion is drawn. The results of this study are based on the results of the analysis and discussion that has been stated, that the empowerment of government officials on work performance in the personnel agency and human resource development of Bombana Regency consists of 2 indicators, namely empowerment of the apparatus consisting of education and training (training) and career development. Then the employee performance achievements consist of quality of work, quantity of work and timing.